2021
DOI: 10.3389/fmed.2020.559811
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C and COVID-19

Abstract: In numerous animal studies, vitamin C has prevented and alleviated viral and bacterial infections. In a few dozen placebo-controlled trials with humans, vitamin C has shortened infections caused by respiratory viruses, which indicates that the vitamin can also influence viral infections in humans. In critically ill patients, plasma vitamin C levels are commonly very low. Gram doses of vitamin C are needed to increase the plasma vitamin C levels of critically ill patients to the levels of ordinary healthy peopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 28 publications
(30 reference statements)
0
34
0
1
Order By: Relevance
“…The respiratory viruses covered in many trials of vitamin C are non-specific and so it is unlikely that the benefits of vitamin C are constrained to a particular respiratory virus or virus group. Thus, it seems likely that vitamin C may also have an effect on the SARS-CoV-2 coronavirus (11,24).…”
Section: Discussionmentioning
confidence: 99%
“…The respiratory viruses covered in many trials of vitamin C are non-specific and so it is unlikely that the benefits of vitamin C are constrained to a particular respiratory virus or virus group. Thus, it seems likely that vitamin C may also have an effect on the SARS-CoV-2 coronavirus (11,24).…”
Section: Discussionmentioning
confidence: 99%
“…The respiratory viruses covered in many trials of vitamin C are non-speci c and so it is unlikely that the bene ts of vitamin C are constrained to a particular respiratory virus or virus group. Thus, it seems likely that vitamin C may also have an effect on the SARS-CoV-2 coronavirus [11,24].…”
Section: Discussionmentioning
confidence: 99%
“…The urine SG of our adult cases was significantly higher than cohort contact children. Although there is as yet no direct evidence indicating that vitamin C is beneficial specifically against COVID-19, but many authors [29] suggested benefits of vitamin C intake and that it should be considered for patients. The prevalence of this concept led to an increase in the intake of vitamin C among patients in exaggerated quantities.…”
Section: Discussionmentioning
confidence: 99%